2020
DOI: 10.3389/fncom.2020.576841
|View full text |Cite
|
Sign up to set email alerts
|

GLSNN: A Multi-Layer Spiking Neural Network Based on Global Feedback Alignment and Local STDP Plasticity

Abstract: Spiking Neural Networks (SNNs) are considered as the third generation of artificial neural networks, which are more closely with information processing in biological brains. However, it is still a challenge for how to train the non-differential SNN efficiently and robustly with the form of spikes. Here we give an alternative method to train SNNs by biologically-plausible structural and functional inspirations from the brain. Firstly, inspired by the significant top-down structural connections, a global random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…This plasticity is biologically-plausible and will also be used as the main credit assignment of SNNs in our NRR-SNN algorithm. Zhao et al (2020) have proposed a similar method, where global random feedback alignment is combined with STDP for efficient credit assignment.…”
Section: Related Workmentioning
confidence: 99%
“…This plasticity is biologically-plausible and will also be used as the main credit assignment of SNNs in our NRR-SNN algorithm. Zhao et al (2020) have proposed a similar method, where global random feedback alignment is combined with STDP for efficient credit assignment.…”
Section: Related Workmentioning
confidence: 99%
“…NALSM8000 achieved a top accuracy of 97.61% (97.49 ± 0.11%) on MNIST, 97.51% (97.42 ± 0.07%) on N-MNIST, and 85.84% (85.61 ± 0.18%) on Fashion-MNIST. Compared to previously reported benchmarks on MNIST and Fashion-MNIST, the NALSM8000 outperformed all brain-inspired learning methods that do not use backpropagation of gradients or its approximation through feedback alignment [72,73], with the exception of [74] for MNIST. While [74] demonstrated that a fully-connected 2-layer spiking network can achieve high accuracy through a combination of biologically-plausible plasticity rules, it is not clear how such an approach would scale to more layers without some form of backpropagation.…”
Section: Larger Liquids Increased Nalsm Accuracymentioning
confidence: 71%
“…Interestingly, incorporating the neuromorphic principles comes at the cost of a decrease in performance for the existing methods. For example, methods that employ continuous feedback computations (Zhao et al 2020;Lillicrap et al 2016) outperformed those that have event-based feedback (Guerguiev, Lillicrap, and Richards 2017;Tavanaei and Maida 2019;Shrestha et al 2019). However, our method achieved a high level of performance without sacrificing any of the neuromorphic principles.…”
Section: Comparing Biograd Against Other Biologically Plausible Appro...mentioning
confidence: 89%
“…The need for separate feedback pathways is alleviated in (Zhao et al 2020) by not only propagating errors directly from the output layer to hidden layers (Nøkland 2016), but also employing multi-compartment neurons that receive feedforward and feedback information in segregated compartments. However, these methods propagate continuousvalued errors, violating the event-based nature of computations.…”
Section: Related Workmentioning
confidence: 99%